2022
DOI: 10.1021/acsami.1c21391
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Stable Composites of Electrospun Nonwoven Mats and Shear-Thickening Fluids

Abstract: To improve the flexibility of the fabric stacks used in protective clothing, shear-thickening fluids (STFs) have previously been incorporated into woven microfiber fabrics to enhance their impact resistance. However, the microfiber−STF composites can exhibit loss of the STF from the composite over time due to the large interstitial spaces between fibers, resulting in limited long-term shape stability. In this study, nonwoven mats of electrospun ultrafine fibers (UFFs) were used in place of woven microfiber fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…A new composite consisting of electrospun ultrafine fibers and STF was developed to improve the shape stability of STF-impregnated fabrics. The composites were demonstrated to be shape-stable with high breakthrough pressure due to the small effective pore size and the high capillary force of UFF membranes [ 154 ]. Chen et al proposed a direct microencapsulation of Ionic-Liquid-based STF and designed a circuit made of Ionic-Liquid-based STF microcapsules-incorporated conductor.…”
Section: Multi-functional Propertiesmentioning
confidence: 99%
“…A new composite consisting of electrospun ultrafine fibers and STF was developed to improve the shape stability of STF-impregnated fabrics. The composites were demonstrated to be shape-stable with high breakthrough pressure due to the small effective pore size and the high capillary force of UFF membranes [ 154 ]. Chen et al proposed a direct microencapsulation of Ionic-Liquid-based STF and designed a circuit made of Ionic-Liquid-based STF microcapsules-incorporated conductor.…”
Section: Multi-functional Propertiesmentioning
confidence: 99%
“…Test results showed that the applied impact force on treated STF-impregnated fabric was less than that on pure STF-impregnated fabric, and thereby the STF properties could affect the cushioning effects of fabrics. Hao et al 74 introduced a new composite consisting of electrospun polyamide ultrafine fiber (UFF) non-woven mats and STF to improve the shape stability of fabrics (Figure 8(b)). Drop impact tests were conducted to characterize the viscoelastic response under a high deformation rate.…”
Section: Drop-weight Impactmentioning
confidence: 99%
“…(a) Low-velocity drop-weight impact testing (Copyright 2019, Elsevier), 84 drop-weight tests on (b), (c) electrospun a non-woven mat/shear thickening fluid (STF) composite (Copyright 2020, American Chemical Society), 74 and (d), (e) a warp-knitted spacer fabric (WKSF)/STF composite (Copyright 2013, Elsevier). 59 …”
Section: Impact Behaviors Of Shear Thickening Fabric Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear thickening gel (STG) is a colloidal functional material whose modulus increases instantaneously with increasing shear rate, and its state transforms from viscous liquid to solid. 4,5 Compared to shear thickening fluid (STF), which is also stimuli-responsive and has been extensively studied, [6][7][8][9] STG is more viscous in its natural state and exhibits better stability. 10 When subjected to impact, the shear thickening effect and viscoelastic deformation of STG results in a massive expansion of the impacted area, while the impact force and energy are diffused and absorbed, 11 and thereby a variety of STG composites have been prepared for impact protection.…”
mentioning
confidence: 99%